Enfermidades infecciosas em comunidade indígena Terena de Mato Grosso do Sul - AGUIAR, José Ivan Albuquerque (2008)
The health conditions of Brazilian indigenous population are few recognized with limited information available. A survey was carried out among indians Terena, people that inhabit on the municipalities of Sidrolândia and Dois Irmãos do Buriti, Estado de Mato Grosso do Sul, Brazil. Was studied the prevalence of infection by intestinal parasites, infection markers for viral Hepatitis A, B and C, and for antibody against the viral diseases; Poliomyelitis 1, 2 and 3, Measles, Yellow Fever and Hepatitis B. The results were stratified by age and revealed that the parasitic infection affects 73.5% of the population studied, with high prevalence of the Blastocystis hominis. In the population above 10 years, more than 90% showed reactivity to the anti-HAV, absence of infection markers for Hepatitis B and C, respectively HBsAg and anti-HCV, and a rate of 16.7% (95% CI 12.6-21.3) for the anti-HBs. The prevalence of neutralizing antibodies against the measles virus and yellow fever virus was 96.7% (95% CI 93.9-98.3) and 91.4% (95% CI 88.0-94.7) respectively. The polio results showed that 62.2% (95% CI 56.5-67.6) 71.7% (95% CI 66.2-76.6) and 63.5% (95% CI 56.5-69.6) had antibodies against the types 1, 2 and 3, respectively, showing vulnerability to B Hepatitis, Yellow Fever and Poliomyelitis.